Electrochemiluminescence in Tryptophan / Tetraphenylborate System for Biosamples Assay - Zholudov, Yu.; Lysak, N.; Xu, G. (ISBC, 2018)
L-tryptophan is one of the most important essential amino acids which role in the human body is invaluable. It participates in maintaining of nitrogen balance in metabolism, in the synthesis of muscle proteins, enzymes, antibodies of the immune system and other biologically active substances. Thus the development of reliable methods for quantitative determination of this compound in biolsamples, foods and medicines is an actual task for today.
Keywords: ECL; coreactant; tryptophan; assay